An automatic procedure to create fuzzy ontologies from users’ opinions using sentiment analysis procedures and multi-granular fuzzy linguistic modelling methods - Morente-Molinera, Juan Antonio; Kou, Gang; Pang, C.; Cabrerizo, Francisco Javier; Herrera-Viedma, Enrique (Information Sciences, 2019)
The high amount of information that users continually provides to the Internet is unorganized and difficult to interpret. Unluckily, there is no point in having high amounts of information that we cannot work with. Therefore, there is a need of methods that sort this information and stores it in a way that can be easily accessed and processed. In this paper, a novel method that uses sentiment analysis procedures in order to automatically create fuzzy ontologies from free texts provided by users in social networks is presented. Moreover, multi-granular fuzzy linguistic modelling methods are used in order to select the best representation mean to store the information in the fuzzy ontology. Thanks to the presented method, information is transformed and presented in an organized way making it possible to properly work with it.
Keywords: fuzzy ontologies; social networks; sentiment analysis; Scopus; JCR